Are the degrees of the best (co)convex and unconstrained polynomial approximations the same? II - Kopotun, K. A.; Leviatan, D.; Shevchuk, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In Part I of the paper, we have proved that, for every $α > 0$ and a continuous function $f$, which is either convex $(s = 0)$ or changes convexity at a finite collection $Y_s = \{y_i\}^s_i = 1$ of points $y_i ∈ (-1, 1)$,$$\sup \left\{n^{α}E^{(2)}_n(f,Y_s):\;n ≥ N^{*}\right\} ≤ c(α,s) \sup \left\{n^{α}E_n(f):\; n ≥ 1 \right\},$$where $E_n (f)$ and $E^{(2)}_n (f, Y_s)$ denote, respectively, the degrees of the best unconstrained and (co)convex approximations and $c(α, s)$ is a constant depending only on $α$ and $s$. Moreover, it has been shown that $N^{∗}$ may be chosen to be 1 for $s = 0$ or $s = 1, α ≠ 4$, and that it must depend on $Y_s$ and $α$ for $s = 1, α = 4$ or $s ≥ 2$.In Part II of the paper, we show that a more general inequality$$\sup \left\{n^{α}E^{(2)}_n(f,Y_s):\;n ≥ N^{*}\right\} ≤ c(α, N, s) \sup \left\{n^{α}E_n(f):\; n ≥ N \right\},$$is valid, where, depending on the triple $(α,N,s)$ the number $N^{∗}$ may depend on $α,N,Y_s$, and $f$ or be independent of these parameters.